Methods For Clustered Microcalcifications Detection In Digital Mammograms - Wan Zaki, Wan Mimi Diyana (2005)
This theis presents the comparison of three automated methods for an early detection of breast cancer that used to detect clusters of microcalcifications (MCCs), which are associated with a high probability of malignancy. The proposed methods are based on several image processing concepts, such as morphological approach, fractal analysis, adaptive wavelet transform, local maxima detection and high -order statistics (HOS) tests.